2021
DOI: 10.5194/acp-21-7791-2021
|View full text |Cite
|
Sign up to set email alerts
|

Soot PCF: pore condensation and freezing framework for soot aggregates

Abstract: Abstract. Atmospheric ice formation in cirrus clouds is often initiated by aerosol particles that act as ice-nucleating particles. The aerosol–cloud interactions of soot and associated feedbacks remain uncertain, in part because a coherent understanding of the ice nucleation mechanism and activity of soot has not yet emerged. Here, we provide a new framework that predicts ice formation on soot particles via pore condensation and freezing (PCF) that, unlike previous approaches, considers soot particle propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 209 publications
(333 reference statements)
3
58
0
Order By: Relevance
“…This shows coherence with the results at warm temperatures (T > HNT) and can be explained by the H2SO4 pore filling effect. Homogeneous freezing of supercooled water in pores is an important step in a PCF activation process (Marcolli et al, 2021;Marcolli, 2014). According to , the homogeneous freezing rate depends on the liquid water activity.…”
Section: H2so4 Coated Mcastblack Soot Ice Nucleation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows coherence with the results at warm temperatures (T > HNT) and can be explained by the H2SO4 pore filling effect. Homogeneous freezing of supercooled water in pores is an important step in a PCF activation process (Marcolli et al, 2021;Marcolli, 2014). According to , the homogeneous freezing rate depends on the liquid water activity.…”
Section: H2so4 Coated Mcastblack Soot Ice Nucleation Resultsmentioning
confidence: 99%
“…Considering its solubility in water and strong hygroscopic ability, H2SO4 coating very likely enhances soot particle surface wettability, i.e. a lower soot-water contact angle (Mahrt et al, 2020b), which plays an important role in PCF (David et al, 2020;Marcolli et al, 2021). In addition, the coating process can alter soot particle morphology and influence the availability of potential pores for PCF at cirrus cloud conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6, 400 nm compacted FW200 soot particles are more effective INPs than the fresh sample as the compacted particles required a lower RH to reach the same AF value at T < 233 K. We ascribe this to an enrichment in small mesopores for compacted FW200 soot particles. After agitation, macropores (> 50 nm) and larger mesopores (> 20 nm) among fresh soot aggregate might be compacted into smaller mesopores which induce inverse Kelvin effect and lead to capillary condensation at RH conditions well below water saturation condition thereby promoting PCF activation, according to soot-PCF framework (Marcolli et al, 2021). Given that physical agitation is the only modification to soot samples, the enhancement of IN ability must result exclusively from the changes in morphology (resulting in mesopore enrichment) induced by soot aggregate compaction.…”
Section: Fresh and Compacted Soot Particle Activation Fraction Curvesmentioning
confidence: 99%
“…There are also differences between FW200 and PR90 IN activities. Firstly, PR90 soot particles are less active INPs compared to FW200 as shown that the same size fresh or compacted PR90 soot particles require a higher RH than that of FW200 soot with the same compaction level to reach the same AF value at the same T. According to the PCF mechanism (Marcolli, 2014;Marcolli et al, 2021), this probably results from the differences in soot sample properties, including sample PSD and watersoot contact angle, both of which are determinators for the PCF mechanism. Thus, PR90 soot PCF process occurs at higher saturation conditions and requires low T if PR90 soot is originally less porous than FW200 and/or of a lower surface wettability.…”
Section: Fresh and Compacted Soot Particle Activation Fraction Curvesmentioning
confidence: 99%
“…During immersion freezing, ice nucleates over a wider temperature range compared with homogeneous freezing of pure water droplets (Peckhaus et al, 2016;Tarn et al, 2018). Heterogeneous freezing curves become even broader when a mixture of different INP types is investigated.…”
Section: Introductionmentioning
confidence: 99%